EDUCATIONAL ENVIRONMENTS AND WEB MINING (International Journal of Engineering and Computer Science, 2013)
At the present time, education environments have two types. These are traditional and virtual education environments. In both the area, one of the important problems is habit analysis and evaluation. In traditional education systems, habit analysis is done easily through observation techniques, whereas in virtual ones analyzing students’ attitudes and habits is a significant problem. Web mining applications, used in providing meaningful information from meaningless habits and surfing in web environments, is the way to overcome this problem. In this study, web mining applications in virtual education environments were formed in accordance with descriptive research method. In conclusion, how web mining is used in education environments was discovered.